Daisy and the trouble with chocolate - Gray, Kes; Sharratt, Nick Parsons, Garry (Red Fox London, 2017)
"Daisy is so excited! She's been picked to look after the class hamsters, Pickle and Pops, over the Easter holidays - and her mum's taking her to Chocolate Land!!! Trouble is, the two things probably shouldn't mix... " --Publisher description